DIVERSITY OF EXOTIC SPECIES IN TWO URBAN FOREST PATCHES IN CURITIBA, PARANÁ - Reis, Allan Rodrigo Nunho dos; Biondi, Daniela; Corte, Ana Paula Dalla; Batista, Antonio Carlos; Miller, Daniel Zambiazzi; Ivasko Júnior, Severo (Floresta, 2024)
Urban forest patches (UFP) face challenges related to climate change and anthropic impacts on natural ecosystems and their biodiversity, mainly due to the presence of invasive exotic species. The objective of this research was to characterize the invasive flora of two urban forest patches located in Curitiba, Paraná. The research was conducted in the Papa João Paulo II and Gutierrez woods, located in Curitiba, Paraná. Ten sample plots of 20x30 m (600 m²) were installed, all individuals with DBH >15 cm were sampled, six in Papa João Paulo II, and four in Gutierrez. A floristic characterization was carried out in each plot, separating native and exotic species. The ecological indices of Shannon-Weaver Diversity, Pielou, Simpson and Jaccard Equability were calculated to quantify vegetation diversity. Floristic analyzes were carried out in an R ambient. Altogether, 546 tree individuals were measured, belonging to 61 species of 31 families. The mean values of the Shannon-Weaver and Pielou indices were higher in Bosque Gutierrez. There was low similarity in floristic composition between sample plots. There were statistically significant differences between the categories of variables, in relation to native and exotic species, and between UFP. The presence of native species still exceeds that of exotic and invasive alien species in both UFP. The exotic invasive species Ligustrum lucidum already has a worrying influence on the ecological sustainability of UFP. The evaluated UFP are going through the process of biotic homogenization in their floristic composition.